2018
DOI: 10.1117/1.jatis.4.2.029001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a discrete-layout bimorph disk elements piezoelectric deformable mirror

Abstract: We introduce a discrete-layout bimorph disk elements piezoelectric deformable mirror (DBDEPDM), driven by the circular flexural-mode piezoelectric actuators. We formulated an electromechanical model for analyzing the performance of the new deformable mirror. As a numerical example, a 21-actuators DBDEPDM with an aperture of 165 mm was modeled. The presented results demonstrate that the DBDEPDM has a stroke larger than 10 μm and the resonance frequency is 4.456 kHz. Compared with the conventional piezoelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A precision micropositioner using piezoelectric components as the actuators can overcome the shortcomings of conventional positioning devices and have unique advantages in micron and sub-micron precision positioning control [6][7][8][9][10]. According to previous research results, piezoelectric actuators could include conventional piezoelectric components [11,12], piezoceramic bimorphs [13][14][15], piezoelectric stacks [16,17] and composite structures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A precision micropositioner using piezoelectric components as the actuators can overcome the shortcomings of conventional positioning devices and have unique advantages in micron and sub-micron precision positioning control [6][7][8][9][10]. According to previous research results, piezoelectric actuators could include conventional piezoelectric components [11,12], piezoceramic bimorphs [13][14][15], piezoelectric stacks [16,17] and composite structures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One kind of the deformable mirrors, called conventional piezoelectric deformable mirror, is usually supported by an array of the stack-type piezoelectric actuators, coupled to a continuous mirrored face sheet (Hom, 1999). The other kind, named unimorph piezoelectric deformable mirror, consists of a glass sheet on the top layer and a piezoceramics layer on the bottom layer, whose two layers are glued together (Shaw et al, 2010; Wang et al, 2018). The unimorph piezoelectric deformable mirror has lower cost and larger stroke (Wnuk et al, 2005), while the conventional piezoelectric deformable mirror has a higher temporal response.…”
Section: Introductionmentioning
confidence: 99%
“…However, both the unimorph piezoelectric deformable mirror and the conventional piezoelectric deformable mirror are not the best candidates for the adaptive optics system of the large telescopes. In our previous works (Wang et al, 2018, 2016; Wang and Yang, 2016), proposed was a discrete-layout bimorph disk elements piezoelectric deformable mirror driven by the Bimorph Circular Flexural-mode Piezoelectric Actuators (BCFPAs). The results have shown that the stroke of the discrete-layout bimorph disk elements piezoelectric deformable mirror is larger than that of the conventional piezoelectric deformable mirrors and no smaller than that of the unimorph piezoelectric deformable mirror; the natural frequency of the discrete-layout bimorph disk elements piezoelectric deformable mirror is higher than that of the unimorph piezoelectric deformable mirror and almost equal to that of the conventional piezoelectric deformable mirror (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%